Supporting Scientific Collaboration: Methods, Tools and Concepts - Jirotka, M; Lee, C; Olson, G (2013)
This paper discusses the interrelationship between e-Science and CSCW in terms of key substantive, methodological and conceptual innovations made in both fields. In so doing, we hope to draw out the existing relationship between CSCW and e-Science research, and to map out some key future challenges where the two areas of research may become more closely aligned. In considering what may be required to draw the two more closely together, the paper focuses primarily on investigations that have been undertaken in two dedicated initiatives into e-Science, along with the key issues emerging from these studies. © 2013 Springer Science+Business Media Dordrecht.